Design requirements for internal departments for provincial students (Journal of the College of Basic Education, 2022)
The completion of university studies and the promotion of the scientific level are among the most important goals that the student seeks when completing his secondary studies, and he is sometimes confronted with the problem of university admission in a university in a far governorate. The importance of acceptable university housing is highlighted here and is required to be provided to students, and that within the requirements of this housing is the provision of adequate services, security, privacy, psychological comfort and adaptation To live independently from parents for the period of study. The research discusses the reality of a number of departments in Iraq, as well as the standards for university housing within the international requirements for housing, and what can be done to develop and improve the services provided to students and most of the problems that students face in the dormitories.